Perlindungan Hukum Terhadap Pemegang Sertifikat Tanah Yang Diterbitkan - Andreas Subiakto; Yurisa Martanti; Andrea Septiyani (Postgraduate of Jayabaya University, 2018)
Land certificate has an important role for the person concerned. The legal certainty of the certificate applicant is based on the state land that was formerly controlled by PT. Kereta Api Indonesia and the concept of legal protection for holders of title certificates issued based on state land rights. The Kebonharjo community as certificate holders have not received legal protection based on Government Regulation No. 24 of 1997 concerning Land Registration. The method used in this research is with socio-legal research approach that comes from collecting data obtained from primary data and secondary data, then analyzed by qualitative analysis method. The research found that the holders of land rights certificates issued based on state land PT. KAI still has not received legal protection because it still uses a negative publicity system (positive elements). Regarding the concept of legal protection for holders of land rights certificates issued based on state land rights, it must be in accordance with the philosophy of Pancasila Law as the basis for realizing the values of justice for the parties and achieving legal protection for land rights holders